2022
DOI: 10.1175/jamc-d-22-0081.1
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Precipitation Data Using Innovative Trend Pivot Analysis Method and Trend Polygon Star Concept: A Case Study of Soan River Basin, Potohar Pakistan

Abstract: The trend analysis approach is adopted for the prediction of future climatological behavior and climate change impact on agriculture, environment, and water resources. In this study, the Innovative Trend Pivot Analysis Method (ITPAM) and Trend Polygon Star Concept Method were applied for precipitation trend detection at eleven stations located in Soan River Basin (SRB), Potohar region Pakistan. Polygon graphics of total monthly precipitation data were created and trends length and slope were calculated separat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 64 publications
0
10
0
Order By: Relevance
“…Overall, the northern part of the basin is dominated by humid and sub-humid climates, while the central and southern parts are dominated by arid and semi-arid climates, respectively. The northern boundary of SRB is surrounded by the Margalla Hills and the Murree Hills, while the southern boundary is covered by a salt range (Hussain et al, 2022). The climate is continental and subtropical, with hot summers and relatively cold winters.…”
Section: Study Area and Data Descriptionsmentioning
confidence: 99%
See 4 more Smart Citations
“…Overall, the northern part of the basin is dominated by humid and sub-humid climates, while the central and southern parts are dominated by arid and semi-arid climates, respectively. The northern boundary of SRB is surrounded by the Margalla Hills and the Murree Hills, while the southern boundary is covered by a salt range (Hussain et al, 2022). The climate is continental and subtropical, with hot summers and relatively cold winters.…”
Section: Study Area and Data Descriptionsmentioning
confidence: 99%
“…The Innovative Trend Pivot Analysis Method (ITPAM) and Trend Polygon Star Concept Method are new trend tests, and only three studies have been reported that used both methods for temperature and precipitation trend analysis (Ceribasi et al, 2021a(Ceribasi et al, , 2021bHussain et al, 2022). The ITPAM determines risk classes by establishing a relationship between data (Ceribasi et al, 2021a).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations